2009
DOI: 10.1007/s10165-009-0217-6
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab treatment reduces the serum levels of interleukin-23 in patients with rheumatoid arthritis

Abstract: In this study, we investigated the effect of the antitumor necrosis factor alpha (anti-TNF-alpha) antibody, infliximab, combined with methotrexate (MTX) and MTX alone on the serum levels of interleukin (IL)-23 and IL-17 in rheumatoid arthritis (RA) patients. Infliximab combined with MTX was administered to 26 patients with RA (infliximab group), and MTX alone was given to 20 patients with RA (MTX group). We evaluated clinical and laboratory parameters, including the Disease Activity Scores of 28 joints (DAS28)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 23 publications
3
23
0
1
Order By: Relevance
“…Our previous studies have also shown that IL-21 could promote LP-CD4 + T cells to differentiate into Th17 cells in CD patients [15]. Thus, the current results revealed a novel antiinflammatory activity of IFX by the reduction of IL-21 expression in the inflamed mucosa of CD patients, and the [29]. Evidence has shown that Th17 cells are identified as a potential subset of Th cells related to the development of autoimmunity and inflammatory responses such as CD, and that IL-21-driven intestinal pathology is associated with increased Th17 cell differentiation [30,31].…”
Section: Discussionsupporting
confidence: 74%
“…Our previous studies have also shown that IL-21 could promote LP-CD4 + T cells to differentiate into Th17 cells in CD patients [15]. Thus, the current results revealed a novel antiinflammatory activity of IFX by the reduction of IL-21 expression in the inflamed mucosa of CD patients, and the [29]. Evidence has shown that Th17 cells are identified as a potential subset of Th cells related to the development of autoimmunity and inflammatory responses such as CD, and that IL-21-driven intestinal pathology is associated with increased Th17 cell differentiation [30,31].…”
Section: Discussionsupporting
confidence: 74%
“…These data suggest that Th17 cells are involved in inflammatory arthritis, regardless of disease stage or treatment, although treatment effects (both increases and decreases) have been observed in other studies [3,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 50%
“…The diminution of IL-17 may be one of the mechanisms of MTX treatment in RA. Previous studies [26,27] have reported that there was no significant difference of serum IL-17 levels between predrug treatment and postdrug treatment. This may be caused by the complex interactions of drugs when MTX is used in combination with other drugs in vivo.…”
Section: Discussionmentioning
confidence: 95%